A DoE Study for Optimization of Control Quality Attributes and Critical Material Attributes in Development of Almotriptan Fast Dissolving Tablet for the Enhancement of Effective Surface Area - Guptha, Prathap Madeswara; Gunda, Raghavendra Kumar; Vanangamudi, Murugesan; Prabahar A, Elphine (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: The primary goal of this study is to increase the effective surface area of Almotriptan and improve disintegration time and diffusion time of the tablet by using a direct compression technique for producing Fast-Dissolving Tablets (FDTs). Materials and Methods: As part of the Quality by Design (QbD) strategy, the Box Behnken Design (BBD) was used as the experimental design. Compression force (factor A), Polyplasdone XL 10 (factor B) and Explosol (factor C) are considered as key control variables. Response factors include Wetting Time (WT), Disintegration Time (DT) and Dissolution Release (%CDR), as well as the Target Product Quality Profile (TPQP). The response surface quadratic model was used to analyze the impact of the factors on three responses factors. Results: The two-way interactions of key control variables were found to have a significant impact on all three responses (at p<0.05). Graphical optimization was carried out using the desirability functions method to achieve low WT, low DT and maximum % CDR. The optimized ADFTs had times of 18.13 sec (WT), 47.84 sec (DT) and 99.2%CDR, respectively. Further optimized ADFT was subjected to in vitro diffusion and findings showed 98.2% diffusion. Conclusion: The increased in effective surface area witnessed through rate of diffusion by selecting optimized range of compression force (151.41MPa) as Critical Quality Attributes (CQAs) and Polyplasdone XL-10 (10 mg) and Explosol (20 mg) as Critical Material Attributes (CMAs).
Keywords: Almotriptan; Compression force; Fast dissolving tablets; Box Behnken design and Quality by design